Tutela inibitória antecipada na ação civil pública ambiental - Chaves, Luciana Oliveira (2011)
In the midst of the evolution from the Liberal State to the Social Democratic State, the collective legal relations and the emergence of the so called "new" rights, the State's duty is no longer of merely declaring rights, It became a agent of execution of these, assuming or intervening in the social and economic life of its citizens. The society previously linked to individual values started to contemplate the collective, with the necessary incorporation of new procedurals arrangements; the establishment of instruments that enable the expansion of justice access, and especially, the hanneling of collective action in the judicial sphere. One of the most prominent of these instruments is the Public Civil Action, a procedural technique that offers greater advantages to the legal protection of the environment, with especial concern to the prevention of damage to its quality, as well as restore what may have already been degraded; and the constant purpose of maintaining an ecologically balanced environment for present and future generations. For that, the use of preventive and swift legal instruments like the anticipated tutelage in the inhibitory action, by the general public, is essential.